Management of public enterprises : with special reference to India - Chatterjee, S. K. (New Delhi : Surjeet Publications, 1982)
This book examines the management of public enterprises with reference to India. It identifies the public sector and compares it with the private sector. In additions describes regulations governing industries and other aspects inovled in the management of these enterprises.
Includes bibliographical references and index.
lje 24/01/2019
Loans
Keywords: Public enterprise; Public sector; Private sector .; India